Freight Forwarder Role: PT. Mitsui-Soko Indonesia in The Process of Importing Electric Motorcycle Sparepart Products (Hs Code: 8501.52) to PT. Pratama Amerta Solutions - Anugrah Putra, M. Rivan (Riviera Publishing, 2024)
International trade has become an increasingly important factor in the global economy today. In this context, the role played by Freight Forwarders in facilitating the movement of goods between countries has become very significant. This research focuses on analyzing the role of PT. Mitsui-Soko Indonesia is a Freight Forwarder company importing electric motor spare part products classified under HS Code 8501.52, imported by PT. Pratama Amerta Solusi. This research aims to identify the contributions made by the Freight Forwarder in improving the smoothness of the import process, provide an overview of the import process, outline the documentation required for importing, and analyze the risks that could occur and their impact on the supply chain and the operational sustainability in the case study of PT. Pratama Amerta Solusi's import through the Freight Forwarder: PT. Mitsui - Soko Indonesia. The research methodology is qualitative and quantitative and employs a case study approach, focusing on the import process of PT. Pratama Amerta Solusi through PT. Mitsui Soko - Indonesia as the Freight Forwarder. Primary data were obtained through direct interviews with representatives from PT. Mitsui-Soko Indonesia, who acted as the import forwarder, while secondary data were gathered from books, national and international journals, previous research, and other credible and relevant sources. The quantitative research was conducted to obtain the magnitude of the impact and the importance of risks in PT's export and import logistics processes. Mitsui - Soko Indonesia.